Classificação climática de Thornthwaite e sua aplicabilidade agroclimatológica nos diferentes regimes de precipitação em Pernambuco - Silva, Alexsandro Oliveira da [UNESP]; Moura, Geber Barbosa de Albuquerque [UNESP]; Klar, Antonio Evaldo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2014)
Knowing the annual climatic conditions is of great importance for appropriate planning in agriculture. However, the systems of climatic classification are not widely used in agricultural studies because of the wide range of scales in which they are used. A series with data from 20 years of observations from 45 climatological stations in all over the state of Pernambuco was used. The probability density function of the incomplete gamma distribution was used to evaluate the occurrence of dry, regular and rainy years. The monthly climatic water balance was estimated using the Thornthwaite and Mather method (1955), and based on those findings, the climatic classifications were performed using the Thornthwaite (1948) and Thornthwaite and Mather (1955) for each site. The method of Kriging interpolation was used for the spatialization of the results. The study classifications were very sensitive to the local reliefs, to the amount of rainfall, and to the temperatures of the regions resulting in a wide number of climatic types. The climatic classification system of Thornthwaite and Mather (1955) allowed efficient classification of climates and a clearer summary of the information provided. In so doing, it demonstrated its capability to determine agro climatic zones.

O conhecimento das condições climáticas é de grande valor para o planejamento agrícola adequado. Entretanto, os sistemas de classificações climáticas são pouco utilizadas no âmbito de estudos agrícolas, devido a grande abrangência das escalas em que são utilizados. Foram utilizadas neste estudo uma série histórica com dados mínimos de 20 anos de observações em 45 estações climatológicas espalhadas por todo Estado de Pernambuco. A função de densidade de probabilidade da distribuição gama incompleta foi utilizada para avaliar a ocorrência de anos secos, normais e chuvosos. O balanço hídrico climático mensal foi estimado pelo método proposto por Thornthwaite e Mather (1955) e com os resultados obtidos foram realizadas as classificações climáticas segundo Thornthwaite (1948) e Thornthwaite e Mather (1955) para cada localidade. Para espacialização dos resultados utilizou-se o método de interpolação de krigagem. As classificações propostas demonstraram-se ser muito sensíveis ao relevo das localidades, aos montantes de chuvas e as temperaturas das regiões resultando em um número abrangente de tipos climáticos. O sistema de classificação climática de Thornthwaite e Mather (1955) permitiu separar eficientemente os climas resumindo as informações geradas com maior clareza demonstrando, dessa forma, capacidade para determinação de zonas agroclimáticas.
Climatic classification of thornthwaite and its agro-climatic feasibility in different precipitation regimes in Pernambuco
Keywords: Water deficit; Evapotranspiration; Irrigation; Deficit hídrico; Evapotranspiração; Irrigação